THE INFLUENCE OF PARAMETERS OF GROUND CONNECTIONS IN FIELD MICROELECTROSOUNDING DEVICE ON ACCURACY OF ELECTRICAL POTENTIAL MEASUREMENTS - REVA М.; ONYSHCHUK, I.; ONYSHCHUK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The result of calculations of the geometric parameters influence of the microelectrosounding and recommendations for their optimal sizes.